Impact of extended-course oral nirmatrelvir/ritonavir in established Long COVID: a case series - Alison K. Cohen; Toni Wall Jaudon; Eric M. Schurman; Lisa Kava; Julia Moore Vogel; Julia Haas-Godsil; Daniel Lewis; Samantha Crausman; Kate Leslie; Siobhan Christine Bligh; Gillian Lizars; JD Davids; et al. (Communications Medicine)
Abstract Background Prior case series suggest that a 5-day course of oral Paxlovid (nirmatrelvir/ritonavir) benefits some people with Long COVID, within and/or outside of the context of an acute reinfection. To the best of our knowledge, there have been no prior case series of people with Long COVID who have attempted longer courses of nirmatrelvir/ritonavir. Methods We documented a case series of 13 individuals with Long COVID who initiated extended courses (>5 days; range: 7.5–30 days) of oral nirmatrelvir/ritonavir outside (n = 11) of and within (n = 2) the context of an acute SARS-CoV-2 infection. Participants reported on symptoms and health experiences before, during, and after their use of nirmatrelvir/ritonavir. Results Among those who take an extended course of nirmatrelvir/ritonavir outside of the context of an acute infection, some experience a meaningful reduction in symptoms, although not all benefits persist. Others experience no effect on symptoms. One participant stopped early due to intense stomach pain. For the two participants who took an extended course of nirmatrelvir/ritonavir within the context of an acute reinfection, both report eventually returning to their pre-re-infection baseline. Conclusions Extended courses of nirmatrelvir/ritonavir may have meaningful benefits for some people with Long COVID but not others. We encourage researchers to study how and why nirmatrelvir/ritonavir benefits some and what course length is most effective, with the goal of informing clinical recommendations for using nirmatrelvir/ritonavir and/or other antivirals as a potential treatment for Long COVID.